Marketing Strategies Applied in Hotel Vasaka Makassar in Rising the Number of Destinations - Mujahid; Syamsul Riyadi; Nasyirah Nurdin; Devita Taruk La’bi (Jurnal Sinar Manajemen, 2024)
This research aims to determine the marketing strategies applied at Hotel Vasaka to increase the number of visitors. The study was conducted at the Vasaka Hotel. The survey period ranges from July to August 2023, using qualitative methods. The survey results showed that the strategy used by Hotel Vasaka is through the products and facilities available at the hotel, the prices offered are quite affordable, and the strategic location and the promotion used are offline and online strategies.